Innovation Patterns and Intellectual Property in SMEs of a Developing Country (2007)
Based on empirical results, this article reopens the discussion about the relationship between intellectual property and innovation in developing countries. Intellectual property grants a monopoly over the commercial exploitation of innovations. Ex-ante, this monopoly may promote innovation but ex-post it may become a disincentive to diffusion and, under certain conditions, to subsequent innovations. After reviewing the terms of the debate in the classical and current literature, the article addresses two empirical issues: first, it characterizes different coexisting innovation patterns of small and medium enterprises in developing country (Colombia); second, it relates these patterns with the innovation performance, intellectual property behavior and other characteristics of these firms.